FACTORS ASSOCIATED WITH SEXUAL VIOLENCE IN CHILDREN IN BAITURRAHMAN DISTRICT, BANDA ACEH CITY - Andriani, Intan; Agustina, Agustina; Anwar, Syafruddin (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: The rise in cases of violations in children's rights has disturbed various parties. Violence against children is any forms of treatment, both physical and psychological, that results in suffering for the children. Data from the Center for Integrated Services for the Empowerment of Women and Children (P2TP2A) Kota Banda Aceh in 2019 showed that there were 19 cases of sexual violence in which the perpetrators included people from their village, boyfriends, drivers, older brothers, and other close relatives . The age range for children who experience sexual violence is 5-15 years. Conditions of sexual violence have a huge psychological impact, such as fear, shame, sadness, and then easily get angry. This research aims to determine the factors that influence sexual violence against children in Baiturrahman District, Kota Banda Aceh Method: This type of research is descriptive- analytical with a cross- sectional design. The population in this study was all children aged 10-15 years in Baiturrahman District totaling 10,834 children. Sampling used proportional sampling technique. The number of samples after using the Slovin formula was 82 respondents. Data collection was carried out from 3-13 July 2020 using a questionnaire. Analysis of data used chi-square using the SPSS 22 program. Results: The results showed that there was no relationship between gender (p value=0.679), parenting status (p value=0.534), and reproductive health knowledge (p value=0.647), with violence sexual relations with children. There is a relationship between broken homes (p value=0.01) and parenting style (p value=0.001) with violence against children in Baiturrahman District, Kota Banda Aceh. Recommendation: It is hoped that parents, to take better care of their children to avoid sexual violence and provide the children correct knowledge and understanding of their body parts.